1997
DOI: 10.1021/jp9623960
|View full text |Cite
|
Sign up to set email alerts
|

Computational and EXAFS Study of the Nature of the Ti(IV) Active Sites in Mesoporous Titanosilicate Catalysts

Abstract: First principles, nonlocal density functional theory (DFT) calculations within the cluster approximation have been carried out in order to model the formation of Ti active sites in the pores of mesoporous silicas by the reaction of (η 5 -C 5 H 5 ) 2 TiCl 2 with terminal surface silanols. In line with recent experimental observations (Maschmeyer, T.; Rey, F.; Sankar, G.; Thomas, J. M. Nature, 1995, 378, 159), the calculations predict that, after calcination, the dominant surface Ti species is the (≡SiO) 3 TiOH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
134
0
4

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 135 publications
(150 citation statements)
references
References 49 publications
12
134
0
4
Order By: Relevance
“…It was possible to structurally follow not only the synthesis of the surface-grafted active catalyst from its precursor half-sandwich complex, but also to ascertain that the original four-coordinated active site becomes six-coordinated under reaction conditions, and to watch the activity being lost by water uptake and then to follow the reactivation of the catalyst subsequent to water removal, effectively identifying the 'pre-natal, post-natal, dead and resurrected' states of the catalyst. From these studies, it was clear that the active sites are atomically dispersed titanol centres (Marchese et al 1997(Marchese et al , 1999Sinclair et al 1997;Thomas et al 1999). To investigate whether it was indeed possible to prepare the postulated intermediate half-sandwich titanocene complex and whether isolated titanols are, in fact, active catalytic centres, a number of studies were reported which sought to answer these questions using titanium complexes of silsesquioxanes as model compounds.…”
Section: Titanium-silsesquioxanesmentioning
confidence: 99%
“…It was possible to structurally follow not only the synthesis of the surface-grafted active catalyst from its precursor half-sandwich complex, but also to ascertain that the original four-coordinated active site becomes six-coordinated under reaction conditions, and to watch the activity being lost by water uptake and then to follow the reactivation of the catalyst subsequent to water removal, effectively identifying the 'pre-natal, post-natal, dead and resurrected' states of the catalyst. From these studies, it was clear that the active sites are atomically dispersed titanol centres (Marchese et al 1997(Marchese et al , 1999Sinclair et al 1997;Thomas et al 1999). To investigate whether it was indeed possible to prepare the postulated intermediate half-sandwich titanocene complex and whether isolated titanols are, in fact, active catalytic centres, a number of studies were reported which sought to answer these questions using titanium complexes of silsesquioxanes as model compounds.…”
Section: Titanium-silsesquioxanesmentioning
confidence: 99%
“…Detailed spectroscopic and computational studies have confirmed that (ϵSi-O) 3 TiCp is more likely to form than (ϵSi-O) 2 TiCp 2 . [13] To the best of our knowledge, no studies have yet been made of the effect of the presence of an interannular bridge on the anchoring process, or the catalytic properties, of the grafted product. in either dichloromethane (method a) or THF (method b).…”
Section: Synthesis and Spectroscopic Characterisationmentioning
confidence: 99%
“…Consequently it was found that the reactivity of the TS-1 catalyst can be emphatically associated with the tetrahedral nature of the titanium site. Similarly Ti-MCM-41 (also possessing tetrahedral titanium active centres) has been found to be highly active in a range of oxidation reactions 46 using peroxides as oxidants. In both cases, the tetrahedral titanium, being coordinatively unsaturated, is able to activate the peroxide species, creating desirable transition-states in the vicinity of the active centre for subsequent activation of the substrate molecule (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…54 A similar synthetic strategy can be used to form well defined, isolated active sites and has been demonstrated by grafting titanocene dichloride onto the inner walls of M41S, to generate the Ti MCM-41 catalyst. 46 Here, instead of using a complex nanocluster as a precursor, an isolated organometallic species (titanocene dichloride) was used. Whilst such a strategy has been highly effective at the laboratory scale, industrial scale-up for bulk chemistry applications has proved expensive and often difficult to manipulate, due to the delicate air-sensitive nature of the reagents and precursors.…”
Section: Introductionmentioning
confidence: 99%